FDFT1 inhibits macrophage M1 polarization and promotes colorectal cancer progression - GAO Yuan; HUANG Yulan; ZHAO Kun (陆军军医大学学报)
Objective‍　‍To screen the targets related to the metabolic enzymes involved in the cholesterol synthesis pathway that inhibits the polarization of macrophages towards M1 phenotype, and verify the intervention effects and underlying mechanisms in colorectal cancer cells. Methods‍　‍Mouse colorectal cancer MC38 cells were divided into control group (si-NC) and experimental groups (the expression of enzymes in cholesterol synthesis pathway was interfered with siRNA for corresponding targets). RT-qPCR was used to detect the mRNA levels of corresponding targets in MC38 cells after transfection. After peritoneal macrophages were extracted from male C57BL/6 mice (6 weeks old, weighing 13~18 g), the macrophages were then treated with the conditioned media of MC38 cells transfected with different siRNAs for 48 h. RT-qPCR was employed to detect the mRNA levels of IL-1β, IL-6 and TNF-α in the macrophages so as to evaluate the effect of the culture media on the M1 polarization. MC38 cells were divided into control groups (OE-NC and sh-NC), farnesyl-diphosphate farnesyltransferase 1 （FDFT1) overexpression group (OE-FDFT1) and FDFT1 knockdown group (sh-FDFT1). RT-qPCR was applied to detect the mRNA expression of FDFT1, and Western blotting was conducted to measure the protein level of FDFT1. C57BL/6 mice were subjected randomly to construct a subcutaneous tumor-bearing model and a model of intraperitoneal metastatic tumor (n=5) respectively. The growth of tumor mass was then measured. Flow cytometry was used to observe the proliferation and apoptosis of MC38 cells, and Transwell assay to detect migration ability of MC38 cells. Five C57BL/6 macrophage-depleted mice (established with injection of clodronate liposome suspension through tail vein) received intraperitoneal implantation to construct a metastasis model, and then the obtained tumor masses were then weighted. Results‍　‍Compared with MC38 cells after si-NC transfection, the mRNA levels of corresponding targets in MC38 cells in the experimental groups were significantly reduced (P<0.05). Significant increases were found in the mRNA levels of IL-1β, IL-6 and TNF-α of the macrophages with FDFT1 interference than the control cells (P<0.05). There were no statistical differences in the proliferation, apoptosis and migration of MC38 cells in the control group (OE-NC and sh-NC) and the cells of the FDFT1 overexpression group and FDFT1 knockdown group (P>0.05). In both the subcutaneous tumor-bearing model and the model of intraperitoneal metastatic tumor, the mass weight was significantly heavier in the OE-FDFT1 group than the OE-NC group (P<0.01), and was notably smaller in the sh-FDFT1 group than the sh-NC group (P<0.01). For the macrophage-depleted mouse tumor model, no remarkable change was observed in the tumor weight between the OE-FDFT1 group and the OE-NC group as well as the sh-FDFT1 group and the sh-NC group. Conclusion‍　‍FDFT1, the metabolic enzyme in the cholesterol synthesis pathway of colorectal cancer tumor cells, is a potential target for tumor immunotherapy targeting macrophages, which promotes tumor progression by regulating macrophages.